THEORETICAL ASPECTS OF ENVIRONMENTAL INSURANCE - Ромашко, Олександра; Крихівська, Наталія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article analyzes different points of view on defining the essence of the concept of "environmental insurance". It is established that in the scientific literature there is no unambiguous interpretation of the essence of this category, in addition, there is no legislative enshrinement in regulations of its content. Based on the study, the social, economic, financial, legal and institutional aspects of environmental insurance are identified. The characteristics of the basic theoretical principles of environmental insurance are outlined, namely: goals, objectives, object, subjects, insurance risk and insured event. It is determined that the main purpose of environmental insurance is to ensure liability insurance for damage caused by an individual or legal entity as a result of sudden, unforeseen and unintentional pollution. Among the tasks of environmental insurance are: ensuring the rights of third parties who have suffered damage as a result of an accident at a dangerous object, by obtaining compensation for damage to life, health and property; protection of property interests of owners of dangerous industrial enterprises by making claims to them by persons affected by the accident. It is established that the object of environmental insurance are the property interests of policyholders or third parties, and among the subjects are: policyholders, insurers, victims and associations of insurers (insurance pools). It is determined that the insurance risk in environmental insurance will be environmental risk, and the insured event is the fact of harm to life, health or property of third parties or the environment.The article also presents the main characteristics of environmental insurance. The functions of ecological insurance are described, namely: compensatory, preventive, social, control and information.